The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1515/sug-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Flucht – Migration – Gender

Abstract: Zusammenfassung Im vorliegenden Beitrag wird vor dem Hintergrund diskursiv verhandelter Topoi über Geflüchtete untersucht, inwiefern Sportlehrkräfte geflüchtete Schüler*innen als ‚Andere‘ wahrnehmen. Angesichts der binären Geschlechterordnung, die sowohl im Sport als auch im Diskurs um Geflüchtete reproduziert wird, liegt der Schwerpunkt hierbei auf der geschlechterbezogenen Konstruktion von ‚Anderssein‘. Dafür werden der Forschungsstand und konstruktivistische und postkoloniale Theoriebezüge skizziert sowie 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
3
0
3
Order By: Relevance
“…They had to look for other ways to connect with peer groups, such as through music, which underlines that school sports limit participation opportunities for female students from refugee backgrounds. The results of an interview study with PE teachers by the authors of this paper on inclusion and the management of heterogeneity in German PE indicate that teachers perceive students from refugee backgrounds in PE in a stereotypical way and formulate gender-typical attributions along the hierarchical gender order particularly strongly (Bartsch et al, 2019). This study also showed that postcolonial patterns are reflected in PE by using it to teach obedience, convey Western Christian norms, and promote monolingual standards (Bartsch, accepted).…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…They had to look for other ways to connect with peer groups, such as through music, which underlines that school sports limit participation opportunities for female students from refugee backgrounds. The results of an interview study with PE teachers by the authors of this paper on inclusion and the management of heterogeneity in German PE indicate that teachers perceive students from refugee backgrounds in PE in a stereotypical way and formulate gender-typical attributions along the hierarchical gender order particularly strongly (Bartsch et al, 2019). This study also showed that postcolonial patterns are reflected in PE by using it to teach obedience, convey Western Christian norms, and promote monolingual standards (Bartsch, accepted).…”
Section: Literature Reviewmentioning
confidence: 86%
“…The data presented in this article is based on a qualitative interview study with 31 PE teachers conducted between February and July 2017 in the federal state of North Rhine-Westphalia in Germany. The analysis carried out here is intended to deepen, broaden, and link the findings of two previous articles (Bartsch, accepted;Bartsch et al, 2019). The study was part of the overarching research project "Schulsport2020" [School Sport 2020], which aims to support both prospective and current PE teachers in dealing with heterogeneous learning groups and to promote equal participation in PE.…”
Section: Methodsmentioning
confidence: 99%
“…Solche "Othering-Prozesse" durch Sportlehrkräfte wurden z. B. bereits hinsichtlich Schülerinnen mit Fluchterfahrungen untersucht (Bartsch, Hartmann-Tews, Wagner, & Rulofs, 2019 (Shogan, 1998). Das Wahrnehmen von Unterschieden zwischen Schüler*innen kann also via Normalitätsanspruch und defizitärer Abweichungszuschreibung Einfluss auf soziale Chancen haben, zudem über die Verteilung von Ressourcen und die Zuschreibung sozialer Positionen mitentscheiden und somit bedeutsame soziale Ungleichheiten konstituieren.…”
Section: Begriffliche Einordnung Und Theoretischer Hintergrundunclassified
“…B. Bartsch et al, 2019;Burrmann, 2017). In Studien zeigt sich des Weiteren die Zugehörigkeit zu einem sozialen Milieu oder einer sozialen Schicht (Frohn, 2007;Thomas & Leineweber, 2018a, 2018b Lutz, 2006;Lutz & Wenning, 2001;Trautmann & Wischer, 2011).…”
Section: Forschungsstand Und Systematisierungunclassified
See 1 more Smart Citation